Fourier Multipliers on Triebel-Lizorkin-Type Spaces. (26th February 2012) - Yang, Dachun; Yuan, Wen; Zhuo, Ciqiang
Abstract : The authors study the mapping properties of Fourier multipliers, with symbols satisfying some generalized Hörmander's condition, on Triebel- Lizorkin-type spaces and Triebel-Lizorkin-Hausdorff spaces. To this end, the authors first establish a new characterization of these spaces via some generalized (weighted)g λ ∗ functions, which essentially improves the known result for Triebel-Lizorkin spaces even whenτ = 0 . Applying this new characterization, the authors then obtain the boundedness of Fourier multipliers on Triebel-Lizorkin-type spaces and Triebel-Lizorkin-Hausdorff spaces, which also give a new proof of the Sobolev embedding theorems for these spaces.